Preparation and Properties of Waterproof Coated Fabrics using Non-Woven Fabric as Base Material - RAMAIAH, GURUMURTHY.B.; CHILLAL, PARASHURAM. S; P. ARI, ASHOK. (International Journal of Psychosocial Rehabilitation, 2020)
Waterproof coated fabrics find numerous engineering applications in day to day life. In this research work acrylic polymer coating material is used with non-woven fabric as base material to develop a waterproof coated fabric. Non-woven fabric with varying layers and thickness is used in preparation of waterproof coated fabrics. Roller method of coating is employed in this research to develop waterproof coated fabrics. Numerous properties like water repellency tests, thickness test, chemical tests, peeling test, Air permeability test, coating hardness tests, thermal property tests and SEM test to observe changes in surface morphology of coated fabrics is employed. Results show that the coated fabrics possess good water repellency characteristics, resistance to chemical degradation, breaking strength, and excellent durability for wear and tear.